CAMEROON FIGHTING BOKO HARAM - KOUMA, J.G. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
This study proposes to retrace Boko Haram atrocities in Cameroon as well as the history of international cooperation against the Islamist sect since the declaration of the war against it in 2014. The principal internal counter-terrorist efforts are shown, including establishement of “Operational Com-mand” missions, partial reorganization of the territorial map of the army’s command, the expansion of defense policy at the subregional level and the gradual redefinition of military, the allocation of re-sources and tools adapted to these new missions. Cameroon engages in a process of multilateralization of the challenges of counter-terrorism coopera-tion, which gives a new dimension to the action of the defense and security forces as well as the multi-lateralization of the stakes of cooperation. The role of major powers and the countries of the subregion as well as the African Union and the United Nations is revealed. Cameroon is a traditional beneficiary of French military assistance. Counter-terrorist assistance also came from Russia, US, UK and Germany. The role of the Multinational Joint Task Force of Commission of the Lake Chad Basin (LCBC) is shown. The author also shows that the war against Boko Haram seems to produce exceptional results that force both admiration and criticism of the Cameroonian people and the international community. The case of criticism by the NGO Amnesty International is analysed in details.